The dual role of polyethylene glycol-simulated drought stress in Stevia rebaudiana (Bertoni): growth reduction and integrated physiological, biochemical, and steviol glycoside responses - Shafiq Hussain; Mehran Ali; Muhammad Zahid; Simone Ribeiro Lucho; Caroline Dambroz; Joyce Dória (Physiology and Molecular Biology of Plants, 2026)
Stevia rebaudiana Bertoni is a globally recognized natural sweetener owing to its zero-calorie steviol glycosides (SGs). However, drought stress, one of the leading abiotic constraints to crop productivity, adversely affects stevia growth and development, while simultaneously altering its biochemical composition. This review highlights the impact of polyethylene glycol (PEG)-induced drought stress on stevia, with particular emphasis on agronomic traits, metabolites, antioxidant activities, and SGs biosynthesis. PEG-mediated stress reduces key growth parameters, such as plant height, biomass, and leaf area, but in some cases, it promotes root elongation as an adaptive strategy to optimize water uptake. Such alterations are accompanied by biochemical adjustments, notably the up-regulation of antioxidant enzymes, such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), which neutralize reactive oxygen species (ROS)-induced oxidative stress. Moreover, PEG stress enhances the accumulation of secondary metabolites, such as phenolic, flavonoids and terpenoids, thereby improving antioxidant potential and stress tolerance. Notably, PEG-induced drought stress shapes SG biosynthesis through the up-regulation of the methylerythritol phosphate (MEP) pathway and the differential expression of key SG-related genes. Such modulation frequently increases SG accumulation, thereby strengthening their medicinal and economic value. Overall, this review covers the dual nature of PEG-induced drought stress: while limiting agronomic performance, enhances SGs biosynthesis and antioxidant capacity. Gaining insights into these mechanisms will facilitate the development of optimized cultivation strategies under water deficit conditions. Future research should prioritize molecular breeding and advanced biotechnological approaches to enhance drought tolerance and maximize the production of bioactive metabolites in stevia.

Retraction notice to “Phosphorus elevation erodes ectomycorrhizal community diversity and induces divergence of saprophytic community composition between vegetation types” [Sci. Total Environ. 793 (2021) 148502] - Muhammad Khalid; Baoming Du; Haoxin Tan; Xinxin Liu; Lantian Su; Saeed-ur-Rahman; Mehran Ali; Chunjiang Liu; Ningxiao Sun; Nan Hui (Science of The Total Environment, 2026)

Redox-responsive goethite-modified biochar regulates cadmium and arsenic translocation in rice via irrigation-driven iron plaque dynamics - Iftikhar Ali Ahmad; Sharjeel Haider; Muhammad Mehran; Zaryab Murad; Adnan Mustafa; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Research, 2026)

Long-term green manure incorporation increases soil carbon sequestration and improves aggregate stability by changing organic carbon components - Yulu Chen; Li Huang; Shaomin Huang; Tengfei Guo; Shuiqing Zhang; Doudou Guo; Xiao Song; Shijie Ding; Muhammad Mehran; Yongqiang Yang; Ke Yue; Sumiao Su; et al. (Soil and Tillage Research, 2026)

Sustainable Management Practices for Maximizing Productivity and Quality in Dual-Purpose Cereal Systems - Maaz Khan; Muhammad Arif; Fazal Munsif; Nazir Ahmad Khan; Muhammad Mehran Anjum; Mehran Ali (International Journal of Plant Production, 2026)

Gypsum-integrated, goethite-modified biochar enhances Cd and As immobilization in contaminated paddy soil under contrasting redox conditions - Iftikhar Ali Ahmad; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Geochemistry and Health, 2026)

Improving Nitrogen Efficiency and Photosynthesis in Wheat Using integrated Nitrogen Management and Modified Geometry - Uzair Ahmed; Muhammad Waseem Abbas; Jalal Bayar; Irshad Ali Khan; Aneela Tahmeed; Muhammad Mehran Anjum; Nawab Ali; Gul Roz Khan; Hazrat Usman; Mahmoud F. Seleiman (Journal of Soil Science and Plant Nutrition, 2025)

Co-utilization of green manure with straw return enhances the stability of soil organic carbon by regulating iron-mediated stabilization of aggregate-associated organic carbon in paddy soil - Muhammad Mehran; Li Huang; Mingjian Geng; Yafen Gan; Jinyun Cheng; Qiang Zhu; Iftikhar Ali Ahmad; Sharjeel Haider; Adnan Mustafa (Soil and Tillage Research, 2025)

A novel F-box gene, SlSE2.2, is responsible for the stigma exsertion degree in tomato (Solanum lycopersicum) - Pan Zhao; Yanhong Zhang; Zhengliang Sun; Baohui Cheng; Liangzhe Meng; Tayeb Muhammad; Yuhe Yao; Muhammad Mehran Abbas; Xiangqiang Zhan; Fei Zhang; Yan Liang (Plant Science, 2025)

Simultaneous adsorption of cadmium and arsenic by goethite-modified rice straw-derived biochar in water and soil: interactive ion effects and co-adsorption mechanism - Iftikhar Ali Ahmad; Hongqing Hu; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Fei Miao; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Ayaz Ali (Environmental Monitoring and Assessment, 2025)

Comprehensive approaches to heavy metal bioremediation: Integrating microbial insights and genetic innovations - Mehran khan; Mir Muhammad Nizamani; Muhammad Asif; Ali Kamran; Guandi He; Xiangyang Li; Sanwei Yang; Xin Xie (Journal of Environmental Management, 2025)

CRISPR-Cas9 based molecular breeding in crop plants: a review - Muhammad Ikram; Abdul Rauf; Muhammad Junaid Rao; Muhammad Faizan Khurram Maqsood; Muhammad Zeeshan Mola Bakhsh; Maaz Ullah; Maria Batool; Muhammad Mehran; Maryam Tahira (Molecular Biology Reports, 2024)

Biochar-based adsorption for heavy metal removal in water: a sustainable and cost-effective approach - Jalal Bayar; Nawab Ali; Younsuk Dong; Uzair Ahmad; Muhammad Mehran Anjum; Gul Roz Khan; Muhammad Zaib; Arshad Jalal; Rovaid Ali; Liaqat Ali (Environmental Geochemistry and Health, 2024)

Corrigendum: Drought-induced adaptive and ameliorative strategies in plants [Chemosphere 364 (2024) 143134] - Sharjeel Haider; Khadija Bibi; Venuste Munyaneza; Hao Zhang; Wen Zhang; Ayaz Ali; Iftikhar Ali Ahmad; Muhammad Mehran; Fangsen Xu; Chunlei Yang; Jinpeng Yang; Guangda Ding (Chemosphere, 2024)

Drought-induced adaptive and ameliorative strategies in plants - Sharjeel Haider; Khadija Bibi; Venuste Munyaneza; Hao Zhang; Wen Zhang; Ayaz Ali; Iftikhar Ali Ahmad; Muhammad Mehran; Fangsen Xu; Chunlei Yang; Jinpeng Yang; Guangda Ding (Chemosphere, 2024)

Futuristic Streamflow Prediction Based on CMIP6 Scenarios Using Machine Learning Models - Basir Ullah; Muhammad Fawad; Afed Ullah Khan; Sikander Khan Mohamand; Mehran Khan; Muhammad Junaid Iqbal; Jehanzeb Khan (Water Resources Management, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Variants in FREM1 and trisomy 18 identified in a neonatal progeria patient - Saima Siddiqi; Noor ul Ain; Mehran Kauser; Zahra Mukhtar; Muhammad Ansar; Muhammad Umair (Molecular Biology Reports, 2023)

Green supply chain management and firm sustainable performance: The awareness of China Pakistan Economic Corridor - Haseeb Ur Rahman; Muhammad Zahid; Mehran Ullah; Mamdouh Abdulaziz Saleh Al-Faryan (Journal of Cleaner Production, 2023)

Distinct climatic regions drive antibiotic resistance genes dynamics across public parks and pristine soil ecosystems - Muhammad Khalid; Xinxin Liu; Bangxiao Zheng; Lantian Su; D. Johan Kotze; Heikki Setälä; Mehran Ali; Asad Rehman; Saeed-ur- Rahman; Nan Hui (Journal of Cleaner Production, 2023)

Development of high-capacity surface-engineered MXene composite for heavy metal Cr (VI) removal from industrial wastewater - Umair Ali Asif; Khalid Mahmood; Salman Raza Naqvi; Muhammad Taqi Mehran; Tayyaba Noor (Chemosphere, 2023)

Development of low-carbon alkali-activated materials solely activated by flue gas residues (FGR) waste from incineration plants - Muhammad Riaz Ahmad; Chandra Sekhar Das; Mehran Khan; Jian-Guo Dai (Journal of Cleaner Production, 2023)

An effective deep learning model for ship detection from satellite images - Aaqib Mehran; Samabia Tehsin; Muhammad Hamza (Spatial Information Research, 2023)

Applications of machine learning in thermochemical conversion of biomass-A review - Muzammil khan; Salman Raza Naqvi; Zahid Ullah; Syed Ali Ammar Taqvi; Muhammad Nouman Aslam Khan; Wasif Farooq; Muhammad Taqi Mehran; Dagmar Juchelková; Libor Štěpanec (Fuel, 2023)

WS2-embedded MXene/GO hybrid nanosheets as electrodes for asymmetric supercapacitors and hydrogen evolution reactions - Sajjad Hussain; Dhanasekaran Vikraman; Zulfqar Ali Sheikh; Muhammad Taqi Mehran; Faisal Shahzad; Khalid Mujasam Batoo; Hyun-Seok Kim; Deok-Kee Kim; Muhammad Ali; Jongwan Jung (Chemical Engineering Journal, 2023)

Efficacy of various natural plant extracts and the synthetic insecticide cypermethrin 25EC against Leucinodes orbonalis and their impact on natural enemies in brinjal crop - Mehran Ullah; Farman Ullah; Muhammad Anwar Khan; Shakil Ahmad; Momana Jamil; Sapna Sardar; Kaleem Tariq; Nazeer Ahmed (International Journal of Tropical Insect Science, 2022)